The Antifungal Potential of Ozonated Extra-Virgin Olive Oil Against Candida albicans: Mechanisms and Efficacy - Simone Augello; Valentina Cameli; Arianna Montanari; Stefano Tacconi; Daniela Uccelletti; Luciana Dini; Emily Schifano (Biomolecules)
The growing emergence of resistance mechanisms and side effects associated with antifungal agents highlight the need for alternative therapies. This study aims to investigate the antifungal potential of ozonated extra-virgin olive oil (EOO) against Candida albicans, with the goal of developing eco-friendly and highly effective treatments based on natural products. Antifungal activity was evaluated via cell viability and biofilm formation assays using Crystal Violet and Sytox green staining. The results showed that EOO reduced C. albicans viability in a dose-dependent manner, achieving over 90% cell death at a 3% (v/v) concentration. Transmission Electron Microscopy (TEM) revealed cell wall structural damage, and ROS levels increased by approximately 60% compared to untreated controls within 10 min of treatment. Additionally, the expression of autophagy-related genes atg-7 and atg-13was upregulated by 2- and 3.5-fold, respectively, after 15 min, suggesting a stress-induced cell death response. EOO also significantly inhibited hyphal formation and biofilm development, thus reducing C. albicans pathogenicity while preserving cell biocompatibility. EOO antifungal activity was also observed in the case of Candida glabrata. In conclusion, ozonated olive oil demonstrates potent antifungal activity against C. albicans by reducing cell viability, inhibiting hyphal and biofilm formation, and triggering oxidative stress and autophagy pathways. These findings position EOO as a promising alternative therapy for fungal infections.